Qualitative analysis of the organisational response of a university hospital during the first wave of the COVID-19 crisis. Issue 2 (14th June 2022) - Harkouk, Hakim; Castel, Patrick; Hervouët, Lucile; Fletcher, Dominique
Abstract : Background: The COVID-19 pandemic has required urgent organisational and managerial adaptation, with hospital medical and administrative leaders under considerable pressure. Methods: At a single French university hospital, we performed a sociological analysis of management adaptation by medical and administrative leaders during the first wave of the COVID-19 crisis. Two sociologists performed interviews with representative members of staff from all the structures involved in managing the crisis to analyse adaptation and the solutions found during this period. Results: The answers collected during interviews were classified into three main topics describing the organisational adaptations of the hospital staff during the COVID-19 crisis: (1) exceptional mobilisation and collaboration; (2) crisis management based primarily on the principle of subsidiarity; and (3) survival of the administrative structure with interventions to support caregivers. Conclusion: This study, focusing on a single hospital, identified a number of factors associated with successful mobilisation in the very specific conditions of this viral pandemic.